Body mass index associated with childhood and adolescent high‐risk B‐cell acute lymphoblastic leukemia risk: A Children's Oncology Group report. (24th July 2020) - Ghosh, Taumoha; Richardson, Michaela; Gordon, Peter M.; Ryder, Justin R.; Spector, Logan G.; Turcotte, Lucie M.
Abstract: Background: Obesity is a risk factor for many adulthood cancers, but its role in childhood, adolescent, and young adult (AYA) cancer is unknown. Childhood and AYA acute lymphoblastic leukemia (ALL) incidence and obesity prevalence have shown concurrent increases. We sought to identify whether obesity may be a risk factor for childhood and AYA ALL. Methods: Characteristics from individuals with ALL, aged 2‐30 years, diagnosed 2004‐2017 and treated on Children's Oncology Group (COG) protocols with available pre‐treatment anthropometric data (N = 4726) were compared to National Health and Nutrition Examination Survey controls (COG AALL17D2). Body mass index (BMI) was defined using standard CDC definitions. Multivariate conditional logistic regression assessed associations between BMI and ALL with additional analyses stratified by sex and race/ethnicity. Results: Among cases (72% high‐risk (HR) B‐ALL, 28% T‐ALL), 5% had underweight, 58% normal weight, 17% overweight, and 20% obesity. Underweight (OR 2.11, 95% CI 1.56‐2.85) and obesity (OR 1.32, 95% CI 1.15‐1.53) were associated with B‐ALL diagnosis. Specifically, obesity was associated with B‐ALL among males (OR 1.57, 95% CI 1.30‐1.91) and Hispanic children (OR 1.78, 95% CI 1.39‐2.29). Obesity was also associated with central nervous system (CNS) involvement. Conclusion: Pre‐treatment obesity is associated with HR B‐ALL among males and Hispanics, as well as with CNS involvement, suggesting common physiology between obesity and leukemogenesis. An association between underweight and ALL was confirmed, likely due to cancer‐associated wasting. These results have important public health implications for obesity prevention and treatment in children and adolescents to reduce cancer risk. Abstract : Deviations in body mass index (underweight and obesity) at the time of diagnosis were significantly associated with a diagnosis of pediatric high‐risk (HR) B‐cell acute lymphoblastic leukemia (B‐ALL) compared to normal weight. Specifically, obesity was associated with HR B‐ALL in males and Hispanics. Obesity was also significantly associated with ALL central nervous system (CNS) involvement.